ChemInform Abstract: Copper‐Catalyzed Oxidative Decarboxylative Couplings of Sulfoximines and Aryl Propiolic Acids. Issue 22 (3rd June 2014) - Priebbenow, Daniel L.; Becker, Peter; Bolm, Carsten
Abstract Electron‐rich aryl propiolic acids are not well tolerated affording the desired N‐alkynylated sulfoximes in less than 20% yield and the Glaser—Hay dimer instead.